Principles and practice of pediatric oncology - Pizzo, Philip A; Poplack, David G (Lippincott Williams & Wilkins, 2002)
Stanford Univ., CA and Harvard Medical School, Boston, MA. Offers expanded discussions of the molecular biology and genetics of pediatric cancers with emphasis, where possible, on those recent findings providing the basis for the development of innovative therapeutic strategies in the future. Previous edition: c1997. DNLM: Neoplasms--diagnosis--Child.
Keywords: onkologie; radiační onkologie; Pediatrics; nádory; Neoplasms; pediatrie; Radiation Oncology; lékařská onkologie; Medical Oncology